The volatile constituents of frankincense – a review. - Mertens, Michaela; Kirchhoff, Eva; Büttner, Andrea (Flavour and Fragrance Journal, 2009)
The smell of frankincense resin and powder, as well as burned frankincense, has been linked to a series of health effects since ancient times. Additionally, frankincense and its fumes are used as a means to induce positive psychophysical effects and well‐being, not only in an ecclesiastical setting but also in traditional medical applications. This review aims to provide an overview of current knowledge of the volatile constituents of frankincense, with explicit consideration concerning the diverse Boswellia varieties. Altogether, more than 300 volatiles in frankincense have been reported in the literature. In particular, a broad diversity has been found in the qualitative and quantitative composition of the volatiles with respect to different varieties of Boswellia. A detailed discussion of the various analytical approaches applied to isolating and analysing the volatile fractions of frankincense is also presented. Copyright © 2009 John Wiley & Sons, Ltd.<br